BioPom film / Nur Syazwani Azlan ... [et al.] - Azlan, Nur Syazwani; Maidun, Azka Afrina; Kamal Idris, Muhammad Fauzi Kamal; Nor Rashidi, Nur Nisa Raihanah; Musa, Nurfathiah (2022)
Fruit is one of the perishable foods with a limited shelf life after being harvested. The delay before they become inedible or unmarketable is influenced by the fruit itself and several environmental factors. The storage temperature, pressure, and relative humidity, as well as the composition of the surrounding gas, are all aspects of environmental factors that need to be considered (Mercier et al., 2019). On the other hand, there is a constantly growing rate of food waste worldwide, of which the most abundant waste is represented by fruit by- products, with a percentage of the residues around 40–50% of the total discards. According to the Food and Agriculture Organisation (FAO) analysis, 1.3 billion of food are wasted annually, and the management of the waste has become a major issue for governments due to the high costs of disposal and treatment (Dilucia et., 2020). To solve this issue, municipalities have decided to simply transport the wastes to landfills and incinerate them, resulting in the reduction of land availability and environmental pollution. Therefore, the development of BioPom film in Malaysia is an innovative initiative in catering to the issues that have been mentioned previously. BioPom film is a product made from pomegranate (Punica granatum) fruit waste able to inhibit the growth of bacteria, retard the oxidation process, prolong fruit shelf life, and at the same time will reduce the abandoned food residue. Pomegranate has been chosen as the main ingredient for film manufacturing due to its high phenolic content, which gives the films a good antioxidant characteristic. In addition, the strong free radical and antibacterial properties of pomegranate peel extract sparked interest in this by-product, thus leading to the development of active films (Dilucia et., 2020). BioPom film can protect the fruits that easily deteriorate after being sliced or harvested, such as apple, banana, avocado, grape and orange, to maintain their freshness